Anti-inflammatory Drug-loaded Electrospun Scaffolds Aimed at Modulating Inflammation in Chronic Skin Wounds - Detamornrat, Usanee (2020)
The prolonged inflammation in chronic wounds is one of the key factors that delays the healing of wounds. During the inflammation phase, neutrophils and macrophages release TNF-α and IL-1β to induce the production or expression of pro-inflammatory mediators: prostaglandin E2 (PGE2), matrix metalloproteinases (MMPs) and nitric oxide (NO). Herein the medicated electrospun scaffolds were developed and aimed to provide a fibrous structure that mimics the architecture of natural extracellular matrix (ECM) to support cell proliferation. In addition, the scaffolds were also designed to deliver anti-inflammatory drugs to inhibit the production/expression of the pro-inflammatory mediators.